Heat losses and thermal stresses of an external cylindrical water/steam solar tower receiver. (25th December 2019) - Qaisrani, Mumtaz A.; Wei, Jinjia; Fang, Jiabin; Jin, Yabin; Wan, Zhenjie; Khalid, Muhammad
Highlights: Solar flux distribution is evaluated around receiver via Monte-Carlo ray tracing tool. Heat losses are evaluated at different wind directions and wind velocities. Combined heat transfer coefficient is evaluated and validated against published data. Computed receiver thermal efficiency (71–77%) is validated against experimental data. Abstract: A receiver serves as a pivotal component in the solar power system as it is responsible for the light-heat conversion. Extensive research has been carried out on cavity receivers while external receivers have been neglected hitherto. Considering this imperative research gap, this work endeavours to narrow the gap by numerically analyzing the thermal performance of an external cylindrical receiver. A methodology is proposed to determine the efficiency of a cylindrical shaped receiver. A heliostat field is simulated using Monte-Carlo Ray Tracing tool to obtain heat flux distribution on the receiver. The peak heat flux obtained, i.e., 425 kW/m 2 lies at the centre of the receiver's front. By designing a tube layout and using boiling heat transfer correlations, temperature at the receiver's surface and water are obtained. Numerical analysis and simulations are then carried out to evaluate receiver's thermal efficiency in six different wind directions and four different wind velocities between 3 m/s and 12 m/s. Natural convection and radiation losses were also considered. Combined heat transfer coefficients obtained through numerical simulations are compared with the previous experimental data. The effect of wind in a single direction is precisely evaluated by dividing the cylinder into panels and evaluating heat losses on each panel individually. The thermal efficiency evaluated oscillates between 71% and 77% based on wind velocity, and the results are validated against the real power plants and experimental data for cylindrical solar receivers. A tube at receiver's centre having the highest temperature gradient is then selected to evaluate thermal stresses. The equivalent stress obtained is less than the yield strength with safety factor > 2.5.